Sites of the Kama Neolithic Culture in the Northern Kama Region - Evgeniia L. Lychagina; Nadezhda S. Batueva; Denis A. Demakov (Археология евразийских степей)
The article provides a description of the sites of the Kama Neolithic culture located in the north of the Perm region. There are 17 such sites, discovered in the region. They are concentrated in two areas: nearby Lake Chusovskoye and in the middle part of the Vishera River. The peculiarities of the location of the sites include their location on the banks of the 4th order rivers and lakes of non-oxbow origin. The Northern Kama region is characterized by short-term campsites of hunters and fishermen with fireplaces and, possibly, ground-based construction such as huts. The pottery assemblages are represented by thick-walled semi-ovoid-shaped ware, decorated with a combed stamp, made by rolling, stepping and stamping techniques. The stone industry is characterized by the use of local raw materials for the manufacture of tools, the flake-blade industry and a variety of retouch with a standard set of basic tools. The Kama Neolithic culture sites in the region date back to the second half of the VI - first half of the V millennium BC. The Khomutovskoe boloto I–II sites can serve as a standard for this culture.